Sistem Informasi Buku Tamu Front End Berbasis Android Pada Badan Pusat Statistik Rokan Hulu - Budi Yanto (RJOCS (Riau Journal of Computer Science), 2018)
Front End Guest Book information system on the Central Bureau of Statistics is very helpful in terms of recording visitor data, by providing an android based mobile devices that exist in the service, then visitors simply fill the self-biodata in accordance with the guidelines and face recording by utilizing the existing front camera on the device and the data is stored in a database. This system is very helpful part of the service in directing where the destination visitors in accordance with the data that has been in the content. The visitor data has reports that can be viewed and printed periodically, meaning that the head of the Central Bureau of Statistics can see the progress of visitors and their goals on a regular basis.